Kearifan Lokal dalam Pembelajaran PAUD untuk Memfasilitasi Profil Pelajar Pancasila - Nini Aryani; Swandra Rahayu (Early Childhood: Jurnal Pendidikan, 2023)
Pancasila Student Profile which has six dimensions, namely; have faith, fear God Almighty and have noble character, be independent, work together, have global diversity, think critically and creatively. The six dimensions are integrated into the learning aspect. At the PAUD level, crafting Pancasila student profiles is carried out using project-based learning so that teachers are expected to be able to design project activities by exploring the cultural potential of each region so that local wisdom can facilitate Pancasila student profiles. The purpose of this research is to find out whether the application of local wisdom in learning to facilitate the profile of Pancasila students is effective. The research method used is descriptive research method with a quantitative approach. The results of this study are indicators of regional specialties 79%, indicators of regional traditional games 81%, and indicators of regional special clothing 82%. The sum of these three indicators can be accumulated with a percentage of 81% which is in the very high category. The results of the hypothesis testing were carried out using a run test. The results of the analysis obtained an Asymp.Sig (2-tailed) value of 1.000 which is greater than 0.05, meaning that H0 is accepted and Ha is rejected. These results can be assumed that the data on local wisdom in facilitating the profile of Pancasila students is arranged randomly.